2019
DOI: 10.1007/s00018-019-03370-4
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiome in tuberculosis susceptibility and treatment response: guilty or not guilty?

Abstract: Although tuberculosis (TB) is a curable disease, it remains the foremost cause of death from a single pathogen. Globally, approximately 1.6 million people died of TB in 2017. Many predisposing factors related to host immunity, genetics and the environment have been linked to TB. However, recent evidence suggests a relationship between dysbiosis in the gut microbiome and TB disease development. The underlying mechanism(s) whereby dysbiosis in the gut microbiota may impact the different stages in TB disease prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 71 publications
3
50
0
1
Order By: Relevance
“…The relationship between TB and carriage of OXA-1, catB3, rmtB and dfrA14 is likely to reflect the impact of gut microbiota disruption arising as a result of prolonged hospital stay and antibiotic therapy. A previous study has reported the relative abundance of gut Firmicutes to be decreased in those with TB, and the prevalence of Proteobacteria to be increased [27]. We observed a reduction in Firmicutes and an increase in Escherichia-Shigella, with the latter correlated with OXA-1, dfrA14 and catB3.…”
Section: Discussionsupporting
confidence: 61%
“…The relationship between TB and carriage of OXA-1, catB3, rmtB and dfrA14 is likely to reflect the impact of gut microbiota disruption arising as a result of prolonged hospital stay and antibiotic therapy. A previous study has reported the relative abundance of gut Firmicutes to be decreased in those with TB, and the prevalence of Proteobacteria to be increased [27]. We observed a reduction in Firmicutes and an increase in Escherichia-Shigella, with the latter correlated with OXA-1, dfrA14 and catB3.…”
Section: Discussionsupporting
confidence: 61%
“…We hypothesize that there is a complex interplay, where a predisposition, stemming from innate immune deficiencies (given this particularly is involved in intracellular bacterial infections and perhaps evolved alongside the resident gut flora), that likely arise from certain deficiencies of the gut microbiome. This has been shown to be the case in tuberculosis susceptibility [32]. Genetic factors, such as the NOD2CARD15 mutations contributes to risk of developing disease, as these enable the pathogenesis of CD and also have been shown to confer an increased risk to mycobacterial infections [33,34].…”
Section: Discussionmentioning
confidence: 97%
“…Here, we focus on the emerging concepts of direct and indirect contributions of the host microbiome to host defense mechanisms against M . tuberculosis infection [ 44 ].…”
Section: Microbiome-immune Crosstalk and Host Control Of M Tuberculosismentioning
confidence: 99%
“…With the growing understanding of how dynamic interactions between microbiota and the host immune system define the development and functions of lymphocytes [ 157 ], there is a growing interest in how the microbiota shapes adaptive immune responses that are critical for the host control of M . tuberculosis infection [ 44 , 158 ].…”
Section: Microbiome-immune Crosstalk and Host Control Of M Tuberculosismentioning
confidence: 99%
See 1 more Smart Citation